44.9k views
2 votes
B(1) = -7
b(n) = b(n – 1) +12
Find the 4 term in the sequence.

User Arnavion
by
4.3k points

2 Answers

5 votes

Answer:

29

Explanation:

b(1) = -7

The 4th term is b(4).

b(n) = b(n - 1) + 12

b(2) = b(1) + 12 = -7 + 12 = 5

b(3) = b(2) + 12 = 5 + 12 = 17

b(4) = b(3) + 12 = 17 + 12 = 29

User Andrey Molochko
by
4.7k points
2 votes

Answer:

b(4)=29

Explanation:

b(1) = -7

b(n) = b(n – 1) +12

b(2) = b(2-1) +12 = b(1)+12 = -7+12 = 5

b(3) = b(3-1) +12 = b(2) +12 = 5+12 = 17

b(4) = b(4-1) +12 = 17+12 = 29

User Alexy
by
5.1k points